Relationship Between Genistein Intake and Body Mass Index (BMI) with Serum Prolactin Levels in Breastfeeding Women in the Area of Benowo and Kenjeran Public Health Centers - Bambang Rahardjo, Widya Kusuma Wardani, Ni Putu Yunita Sri Lestari, Tatit Nurseta, Linda Ratnawati (Pakistan Journal of Medical & Health Sciences, 2022)
Mother’s milk is considered the optimal substance for newborns because it provides complete nutrition, improves infant health, and increases immunity and low incidence of gastrointestinal disease. The development of the alveolar-lobular glands in the breast for the initiation of breastfeeding is the role of the prolactin hormone. Genistein is a type of isoflavonoid whose content is abundant in soybeans, and their processed products (tempeh and tofu) play a role in the synthesis of serum prolactin. Body Mass Index (BMI) indicates maternal nutritional status, which can also affect serum prolactin. This study will discuss the relationship between genistein intake and BMI on serum prolactin levels of nursing mothers. This research uses analytical observational research on 110 breastfeeding mothers in the Benowo and Kenjeran Health Center Work Areas, Surabaya. The results of Spearman’s correlation test showed that there was a significant relationship between genistein intake on maternal serum prolactin levels (p=0.001) and BMI on maternal serum prolactin levels (p=0.036) (Pearson’s test). The estrogenic properties of genistein are very similar to endogenous estrogens, which are thought to increase the formation of maternal serum prolactin levels and its activity which stimulated ductal elongation in mammary gland development. The increase in BMI levels in the body is go with an increase in serum prolactin levels due to the lack of availability of dopamine two receptor (D2R) sites in the body of nursing mothers.